Torn between two worlds: parental experiences of neonatal follow-up for infants with hypoxic ischaemic encephalopathy in India–a qualitative study using interpretative phenomenological analysis. Issue 11 (24th November 2022) - Chandrasekaran, Suja Angelin; John, Hima B; Ross, Benjamin Jeyanth; Arumugam, Asha; Balan, Indira; Samuel, Reema
Abstract : Objective: This study aimed to understand the barriers and facilitators of a neonatal follow-up programme, as perceived by parents of infants born with hypoxic ischaemic encephalopathy (HIE). Design: This study applied a qualitative study design using interpretative phenomenological analysis. It included focus group discussions, face-to-face in-depth interviews and telephonic interviews. Data were analysed using thematic content analysis. Setting: Neonatal follow-up clinic of a tertiary hospital in South India. The study was conducted between March and December 2020. Participants: Five fathers and eight mothers of infants with HIE. Results: Parents of children with HIE are torn between two worlds—an atmosphere of support and one of criticism. Three main themes were identified: (1) neonatal intensive care unit (NICU) stay: distressful versus reassuring experiences; (2) parenthood: supportive versus unsupportive environments; and (3) neonatal follow-up: adherence versus non-adherence. Conclusion: Parents of children with HIE experience sociocultural barriers in the NICU, after discharge and during the follow-up period. These lead to a complex array of emotional and physical consequences that affect parenting and follow-up care.